EARTH OVEN DIPLOMACY: A NEW PARADIGM FOR REGIONAL COHESION - Muhammad Ilham Mustain Murda; Suwarjiya; Tindia Febriyati (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2026)
This study aims to evaluate the effectiveness of Indonesia’s cultural diplomacy in the South Pacific region through the lens of food sovereignty and local traditions. Amidst increasing regional geopolitical complexities, this research proposes the